The uncertainty of the Social Forestry Program in ensuring environmental sustainability in upstream watersheds: a case study of the Sekampung Watershed in Lampung, Indonesia - Fitriani; Arifin, Bustanul; Rosanti, Novi; Somura, Hiroaki; Kazuto, Shima; Yuwono, Slamet Budi; Dermiyati, Dermiyati; Rahmalina, Dian; Lestari, Fitri Yuni; As-Sadili, Abu Hasan (Brawijaya University, 2026)
Building awareness of the importance of proper land management is essential for ensuring the long-term sustainability of upstream watershed areas. This study investigated how land management practices emerge, evolve, and are adopted within the Social Forestry Program in the upstream Sekampung watershed. Exploration was focused on three key aspects: (1) the characteristics of social forestry participants as evidence of ongoing community social transformation; (2) the level of land management across different social, economic, and ecological contexts; and (3) the main factors influencing farmers’ decisions to implement sustainable land management practices. A total of 125 respondents were selected to represent program participants. Land management was categorized into biological and mechanical conservation technologies. A logistic regression model was applied to analyze the probability of farmers adopting conservation practices. Results showed that the Social Forestry Program has facilitated considerable social transformation by strengthening community participation and institutional support. It also promoted diverse land management practices adapted to local conditions. Logistic regression analysis identifies several key determinants influencing farmers’ decisions to adopt soil conservation: coffee plant age, farmer age, family size, land area, education level, and farming experience. The logistic model provides robust analytical grounding. It provides high-quality empirical evidence, interdisciplinary relevance, and policy-relevant insights, making it a valuable addition to the scientific literature on sustainable land management, community forestry, and smallholder resilience.